#JALANKITA: Pemantauan Penyakit Komorbid Penyulit Covid-19 Berbasis Android pada Lansia di Masa Pandemi di Kota Balikpapan: #JALANKITA: Monitoring of Covid-19 Comorbidities on Android Base for the Elderly in the Pandemic Period in the Balikpapan City - Joshua Gaza Dirgantara Tandirogang; Swandari Paramita; Yadi Yadi (Jurnal Sains dan Kesehatan, 2021)
Elderly or commonly referred to as seniors is the age category that has the highest mortality rate due to Covid-19 infection, this is due to not only because of the age factor but also due to comorbid diseases that many elderly suffer from. At present, the use of smartphones has reached the elderly category and has been widely used for daily needs. Seeing this phenomenon, this study has the aim of using an Android-based application in observing and monitoring to see the comorbidities of Covid-19 in the elderly. This study used 112 samples in the city of Balikpapan and aged over 50 years old which was conducted for 3 days in August 2020. This research is a descriptive study and the sampling is purposive sampling. The results in this study showed that the most respondents were 50-59 years of age, the most sexes were women and the most comorbid diseases suffered were high blood pressure or hypertension